Diversification in and around the Atlas Mountains: Insights into the systematics and biogeography of the genus Thalpomena (Orthoptera: Acrididae: Oedipodinae). (22nd January 2022) - Dey, Lara‐Sophie; Hochkirch, Axel; Moussi, Abdelhamid; Simões, Marianna V. P.; Husemann, Martin
Abstract: The genus Thalpomena Saussure comprises nine species and four subspecies and is largely endemic to the Atlas Mountains (North Africa). Here, we used an evolutionary taxonomic approach to differentiate the species of the genus Thalpomena and to reconstruct their biogeographic history. Phylogenetic tree reconstruction based on five molecular markers revealed four distinct clades within the genus Thalpomena . These are not fully in line with the current taxonomy but rather seem to represent lineages defined by their distribution and hind wing banding patterns. All lineages are geographically separated and can be distinguished based on genetic, morphometric and ecological modelling data. Ancestral area reconstruction suggests an origin of the species in the southern regions of the Atlas Mountains (High Atlas to Aures Mountains). Molecular clock analysis promotes the glacial refugia theory, supporting the origin of Thalpomena in the Pliocene, followed by diversification events in the Pleistocene. Abstract : The genus Thalpomena is separated into four lineages, which can be distinguished by their hind wing banding pattern. Further, they can be distinguished in their ecological and morphometrical space. Our analyses assume an origin of the genus in the southern regions of the Atlas Mountains during the Pliocene with several diversification events in the Pleistocene. The species Thalpomena schulthessi is not part of the monophyletic Thalpomena clade from the Atlas Mountains. The taxonomic status of the species needs to be revised in the future.